1999
DOI: 10.1146/annurev.nutr.19.1.407
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Milk Protein Gene Expression

Abstract: Studies using both transgenic mice and transfected mammary epithelial cells have established that composite response elements containing multiple binding sites for several transcription factors mediate the hormonal and developmental regulation of milk protein gene expression. Activation of signal transduction pathways by lactogenic hormones and cell-substratum interactions activate transcription factors and change chromatin structure and milk protein gene expression. The casein promoters have binding sites for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(151 citation statements)
references
References 173 publications
5
143
0
3
Order By: Relevance
“…Thus the synthesis of all but one of the proteins we have classified as milk proteins are turned on in late pregnancy; many of these (see group IFIF 48) do not change between late pregnancy and the first day after birth, increasing sharply on the second day of lactation. Many of these molecules including β-casein, and whey acidic protein are known to be regulated by stat5, a mediator of prolactin signaling, whose mRNA and phosphorylation change little over the period of parturition (Rosen, et al 1999). On the other hand the genes that regulate lipid synthesis are known to be regulated by the transcription factor, SREBP-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the synthesis of all but one of the proteins we have classified as milk proteins are turned on in late pregnancy; many of these (see group IFIF 48) do not change between late pregnancy and the first day after birth, increasing sharply on the second day of lactation. Many of these molecules including β-casein, and whey acidic protein are known to be regulated by stat5, a mediator of prolactin signaling, whose mRNA and phosphorylation change little over the period of parturition (Rosen, et al 1999). On the other hand the genes that regulate lipid synthesis are known to be regulated by the transcription factor, SREBP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Secretory activation is a unidirectional process that takes place with high temporal coherence during the physiological transition from pregnancy to lactation (Neville et al, 2002). Many of the biochemical events in this process have been studied extensively for more than three decades (Wilde et al 1986;Mellenberger and Bauman, 1974;Kuhn, 1968), and it is clear that many of the changes are transcriptionally regulated (Rosen et al 1999). However, the molecular mechanisms that regulate and coordinate these changes in vivo are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The gene encoding the milk protein, ␤-casein, has been used widely as a marker for functional differentiation of MECs. We and others have shown that in both primary mouse mammary epithelial cells and immortalized mammary epithelial cell lines (4 -6), transcription of ␤-casein requires signals from both laminin-111 (previously referred to as laminin-1) and prolactin (1,2,(7)(8)(9)(10). A number of transcription factors, including STAT5, C/EBP␤, and GR, have been shown to be involved in this process (reviewed in Ref.…”
Section: Differentiated Function Of Mammary Epithelial Cells Is Regulmentioning
confidence: 99%
“…Whereas prolactin induction is blocked by the tyrosine kinase inhibitor genistein, expression is stimulated by genistein in cells not treated with hormone. Vanadate, an inhibitor of both phosphatase activity and the glucocorticoid receptor (12,13), blocks lactogenic hormone-induced XOR expression, as does the glucocorticoid receptor antagonist RU38486, suggesting a mode of XOR regulation by lactogenic hormones that is mediated by the glucocorticoid receptor in conjunction with prolactin-induced JAK2/STAT5 and tyrosine kinases (14).…”
Section: Xanthine Oxidoreductase (Xor)mentioning
confidence: 99%